A dual regimen of ritonavir/darunavir plus dolutegravir for rescue or simplification of rescue therapy: 48 weeks’ observational data - Capetti, Amedeo F.; Cossu, Maria Vittoria; Orofino, Giancarlo; Sterrantino, Gaetana; Cenderello, Giovanni; De Socio, Giuseppe V.; Cattelan, Anna Maria; Soria, Alessandro; Rusconi, Stefano; Riccardi, Niccolò; Baldin, Gian Maria; Niero, Fosca P.; et al. (BMC infectious diseases, 2017)
Dolutegravir (DTG) plus darunavir/ritonavir (DRV/r) is a simple combination of drugs that has the best genetic barrier to HIV-1 resistance and may be fit for salvage therapy. All HIV-1-infected subjects treated with DTG plus DRV/r between March 2014 and September 2015 in eight Italian centres were included in the analysis. The main metabolic data, efficacy parameters and safety data routinely collected were provided. This observational study is aimed to assess the efficacy of such approach. The primary end-point was the proportion of subjects achieving or maintaining virologic suppression <50 copies/mL at week 24. Secondary end points were maintaining virologic suppression in the follow-up (weeks 48 and 96) and safety. One hundred and thirty subjects were followed for a median of 56 months. Reasons for switching were simplification (44.6%), viral failure (30%), toxicity (16.9%), non-adherence (4.6%), persistent low-level viremia (3.1%), and drug-drug interaction (0.8%). At baseline, 118 subjects had documented resistance to 1 to 5 antiretroviral classes while 12 had viral rebound at a time when genotypic tests were not yet available. Seventeen and 14 subjects took DRV/r and DTG twice daily, respectively. One subject was lost to follow-up, one discontinued for liver enzymes' elevation, one died of illicit drug abuse and one of cancer-related complications. The proportion of subjects with ongoing HIV replication dropped from 40% to 6.1%. Those with undetectable viral load increased from 38.5% to 76.2%. At week 48, 17.7% had HIV RNA between 1 and 49 copies/mL. The number of subjects with altered serum glucose, creatinine, ALT, AST, total-, HDL- and LDL-cholesterol, triglycerides and MDRD <90 mL/min decreased by week 48, while those having MDRD <60 mL/min remained 4.6%. Overall 90/283 baseline laboratory alterations returned to normality. Switching to DTG plus DRV/r proved to be safe, suppressing viral replication without metabolic impact.